HUBUNGAN ANTARA KEMANDIRIAN DAN KONFORMITAS TERHADAP PENGAMBILAN KEPUTUSAN KARIR MAHASISWA SEMESTER 5 FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI SEMARANG TAHUN 2019 - Irvan Setiawan; Eko Nusantoro (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2020)
Abstract: The number of students entering tertiary institutions every year always increases. The importance of career decision making that must be done by students while in college must be right. This study aims to determine the relationship between independence and conformity on career decision making for 5thÂ  semester studentsÂ  FIP UNNES students in 2019. The design of this study is descriptive correlational. Data were collected using a psychological scale. The sampling technique uses proportioned randem sampling with a significant level of 5%, the total sample used 225 students from a total population of 997 students. Data analysis techniques used multiple linear regression by showing the results of a significant positive relationship between independence and conformity to career decision making with an ignorance result of 0.000 <0.05 and the value for F arithmetic was 61.216> F table 3.04.